Capital and labor income Pareto exponents across time and space - Tjeerd de Vries; Alexis Akira Toda (Luxembourg Income Study (LIS), 2020)
We estimate capital and labor income Pareto exponents across 348 country-year observations that span 51 countries over half a century. We document two stylized facts: (i) capital income is more unequally distributed than labor income; namely, the capital exponent (1-3) is smaller than labor (2-5), and (ii) capital and labor exponents are nearly uncorrelated. To explain these findings, we build an incomplete market model with job ladders and capital income risk that gives rise to a capital income Pareto exponent smaller than but nearly unrelated to the labor exponent. Our results suggest the importance of distinguishing income and wealth inequality.
Keywords: C46; D15; D31; D52; 330; income fluctuation problem; inequality; power law